Predicting Adolescent Depression: The Interrelated Roles of Self-Esteem and Interpersonal Stressors - Fiorilli, Caterina; Grimaldi Capitello, Teresa; Barni, Daniela; Buonomo, Ilaria; Gentile, Simonetta (Frontiers in Psychology, 2019)
Depression in adolescents can lead to social and educational impairment and is a major risk factor for suicide and substance misuse. Thus, predicting and preventing this disorder are extremely important. The current study aimed to analyze the contribution of adolescents’ self-esteem (i.e., quality of interpersonal relationships, control of life events, and management of negative emotions) and interpersonal stressor sources (relationships with parents, teachers, classmates and friends) in predicting several depression manifestations (i.e., depressed mood, sense of inadequacy, and insecurity). Participants were 182 Italian pre-adolescents and adolescents, aged 10 to 14 years, extracted from the general population. They were asked to complete a self-report questionnaire. Results showed that self-esteem was a major factor to be considered in adolescents’ depression. In particular, adolescents’ perception of negative emotion management was the most important protective factor against depression manifestations. Conversely, sources of interpersonal stressors contributed only marginally to depression. Among these, problems with parents and friends increased adolescents’ depressed mood, while troubles with classmates impacted on their sense of inadequacy and insecurity. Implications of these results for positive practices which could enhance adolescents' self-esteem and further expansions of the study are discussed.